Spatial variability of surficial sediments on the northern shelf of the Alboran Sea: the effects of hydrodynamic forcing and supply of sediment by rivers - Bárcenas, P.; Lobo, F. J.; Macías, J.; Fernández-Salas, L. M.; Díaz del Río, V. (Journal of Iberian Geology, 2011)
Alboran Sea, shelf, surficial sediments, backscatter, hydrodynamic modelRecent surficial sedimentary processes led by hydrodynamic forcing and by laterally variable fluvial supplies are investigated in the eastern shelf of the northern Alboran Sea margin. This study highlights the high spatial variability of sedimentary processes in a relatively small area with an abrupt physiography and subjected to a seasonal and strongly fluctuating climate. We correlate seafloor sediments with backscatter distributions extracted from multibeam echo sounder data; in addition, a wind-forced tidal hydrodynamic model provides flow velocity and derived bed shear-stress values under contrasting wind conditions. In the study area, the relative proportions of gravel and muds within a dominantly sandy substratum control surficial backscatter intensities. Across-shelf, the only consistent surficial pattern is depicted by a high backscatter intensity, gravelly sandy infralittoral zone, which is subjected to periodic storm activity. Seaward, significant along-shelf changes of the sediment cover and backscatter intensities appear to be controlled at large by a major physiographic feature (the Carchuna Canyon) which separates a western shelf mostly covered by fluvially-derived sediments and an eastern current-controlled shelf. At a finer scale, the seafloor backscatter response outlines three main shelf environments: storm-dominated, mixed and fluvially-dominated. We found that storm-dominated settings are associated with maximum flow velocities and bed shear stress (during both easterlies and westerlies dominance). The distribution of mixed and fluvially-dominated environments is more complex, as it is related to the interaction of less intense hydrodynamic conditions with laterally changing fluvial supplies from mountainous, short rivers and streams. As a consequence, the surficial sedimentary fingerprints of the two most important regional rivers (Guadalfeo and Adra) are significantly different.